Fabrication of lateral flow immunosensor for the detection of hemoglobin A1c (HBA1C) / Ang Shu Hwang - Ang, Shu Hwang (2016)

(untitled)
The purpose of the study was to provide an alternative point-of-care device for efficient management of diabetic status for type 2 diabetic patients in a resource-limited setting. The study focused on developing functional lateral flow immunosensor for the detection of hemoglobin A1c (HbA1c), the biomarker for the management of type 2 diabetes mellitus. Because human whole blood is a complex matrix with different glycan moieties, a highly selective biosensor towards the specific glycan moiety (HbA1c) in erythrocytes is desirable. In the study, specific pair of antibodies was selected to perform the “sandwich” immunoassay on the paper-based surface, where the assay was performed with lateral flow principle. Besides finding the right pair of antibodies that is highly selective towards HbA1c against all other glycated species in blood, the ideal condition to form stable antibodies-functionalized colloidal gold to transduce the signal, the blocking reagent to minimize the background on the immunosensor, the test line format for visual interpretation and semi-quantitative measurement of HbA1c level, the potential interference from blood, and the dilution factor necessary to lyse the erythrocytes and reduce the viscosity of whole blood on the lateral flow immunosensing platform were investigated. Later, with a calibration curve established, the immunosensor was proved to be able to perform a quantitative analysis on the HbA1c level in human blood, validated by comparing the measurement of HbA1c level by the developed lateral flow immunosensor to that of the standard method and existing pointof- care device commonly used in a clinical setting. Using the established optimized parameters, a new design of sandwich immunoassay format was developed to detect both the total hemoglobin and hemoglobin A1c simultaneously within a test run in a single step. In conclusion, both of the developed prototypes of lateral flow immunosensors have been proven to be clinically operational efficient for measuring HbA1c level, hence, both of them can serve as alternatives for diabetes management in resource-limited setting.